Service Innovation through PANAH SRIKANDI: Realizing Good Governance in Integrated Village Population Administration Registration Services - Saleh, Choirul; Rahmadiansyah, Daniar Rizky; Trilaksono, Hendrik Tri (PT. Riset Press International, 2025)
Population administration services are crucial to good governance, requiring efficiency, accountability, and transparency. To address these needs, the Bojonegoro Regency government introduced an innovation called PANAH SRIKANDI (“Pelayanan Ramah Sistem Registrasi Administrasi Kependudukan Desa Integrasi”). This innovation integrates the population registration process at the village level through a user-friendly digital system. This study aims to analyze the implementation and impact of the PANAH SRIKANDI innovation on good governance practices at the Bojonegoro Regency Population and Civil Registration Office. The research used a qualitative case study approach. Data were collected through in-depth interviews with policymakers and service officers, participatory field observations, and program documentation. Findings show that implementing PANAH SRIKANDI improves the effectiveness and efficiency of population administration services. Due to streamlined procedures and a user-friendly interface, the public finds obtaining documents like e-ID cards and family cards easier. This directly increases citizen satisfaction with these services. Village involvement in the system also speeds up resident data verification. The innovation also strengthens service transparency and accountability and encourages active community participation. However, challenges remain, such as training village staff and improving IT infrastructure. In conclusion, PANAH SRIKANDI significantly supports sound governance principles in Bojonegoro's public population administration services. These findings enrich the theoretical discourse on integrated public service innovation at the local level. They have practical implications, serving as a model that other regional governments can replicate in similar contexts.